Analisis Pesan Moral dalam Cerpen Dua Tengkorak Kepala Karya Motinggo Busye - Jamaludin Jamaludin; Muhammad N. Abdurrazaq; Sobirin Sobirin (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
Short stories are more popular among readers, especially young readers, because they are shorter than novels and contain fewer pages. Numerous moral lessons can be conveyed through short stories. Short stories serve as one of the methods for teaching morality to young readers among other approaches. This thesis examines the moral messages in the short story Dua Tengkorak Kepala by Motinggo Busye. The main research question of this study is: What are the moral messages contained in the short story Dua Tengkorak Kepala by Motinggo Busye? The purpose of this study is to identify the moral messages in the short story Dua Tengkorak Kepala by Motinggo Busye. This research employs a library research approach. Library research involves exploring various literature relevant to the issues being studied. The moral messages in the short story Dua Tengkorak Kepala by Motinggo Busye are categorized into three types: 1) religious moral messages, 2) moral messages regarding the relationship between humans and themselves, including courage, perseverance, responsibility, independence, honesty, and conscience, and 3) moral messages concerning the relationship between humans and others, which include obedience to parents, willingness to sacrifice, respecting others, and helping others.